Preferential Deletion Events in the Direct Repeat Locus of Mycobacterium tuberculosis - Schürch, Anita C. (American Society for Microbiology, 2011)
The “Harlingen” IS6110 restriction fragment length polymorphism (RFLP) cluster has linked over 100 tuberculosis cases in The Netherlands since 1993. Four Mycobacterium tuberculosis isolates that were epidemiologically linked to this cluster had different spoligotype patterns, as well as slightly divergent IS6110 profiles, compared to the majority of the isolates. Sequencing of the direct repeat (DR) locus revealed sequence polymorphisms at the putative deletion sites. These deletion footprints provided evidence for independent deletions of the central region of the DR locus in three isolates, while the different genotype of the fourth isolate was explained by transmission. Our finding suggests that convergent deletions in the DR locus occur frequently. However, deletion footprints are not suitable to detect convergent deletions in the DR because they seem to be exceptional. Deletion footprints in the DR were not described previously, and we did not observe them in any public M. tuberculosis complex sequences. We conclude that preferential deletions in the DR loci of closely related strains are usually an unnoted event that interferes with clustering of closely related strains.